Diseño de un programa de seguimiento de poblaciones de cánidos silvestres en ambientes esteparios de la Patagonia, Argentina - Travaini, A.; Zapata, S.C.; Zoratti, C.; Soria, G.; Escobar, F.; Aguilera, G.; Collavino, P. (Instituto de Ecología, A.C., 2022)
Wildlife management decisions should be based on solid baseline information, with monitoring populations as a necessary activity whenever the management objective is maintaining abundance at a previously stated level. Developing a monitoring program requires careful experimental and statistical considerations in order to get confidence about its capability in detecting predefined trends. Our objective was to develop a monitoring program for two canid species (the Grey Fox Pseudalopex griseus and the Culpeo Fox P. culpaeus), based on visitation indices to bait stations. Using MONITOR software we estimated the sampling effort necessary to detect a 50% decrease in their populations during the next 5 years (annual rate of –12,94%) and during the next 10 years (annual rate of –6,70%), with a minimum power of 80%. We assume that the environmental cost of making a Type II error (failing to detect a real population trend) is greater than that of making a Type I error (sounding a false alarm) and used three alpha levels 0.05, 0.10 and 0.15. We also tested an increasing sampling effort (number of bait stations lines), and activating them during one, two and up to three times in a single year. We fed the MONITOR program with the mean visitation index to the 20 transects activated on several occasions during the previous year in the study area. In order to detect a 50% decrease over the next 5 years, any monitoring program should be based on at least two annual replicates of the bait stations. A monitoring program accessible to the protected area manpower and financial resources and considering the conservation status of the target species would be one developed to detect a 50% decrease over the next 10 years, activating 16 lines once a year, during two or three consecutive nights and an alpha of 0.10. We also discuss alternatives to use only the first nigh of visit in order to assimilate bait stations to scent stations and make these results comparable with other studiesin Patagonia, Argentina. Monitoring programs like the one presented here would be valuable to help managers when deciding about harvest quotas for the fur trade, or anticipating conflicts and solutions with sheep rangers by detecting increasing trends in Culpeo populations.